Prevalence of metabolic syndrome and its components among the teaching faculty of Allama Iqbal Medical College and Jinnah Hospital Lahore - Roomi, Mudassar Ali; Kamran, Haneen; Bilal, Ahmad; Minhas, Umm-e-Aimen; Tahira, Sameen; Zafar, Hafiz Muhammad Qasim (Journal of University Medical & Dental College, 2024)
BACKGROUND & OBJECTIVES: Metabolic syndrome and its components are established risk factors for type-2 diabetes mellitus and cardiovascular diseases. The Objectives of the current study were to assess the mean values of cardiometabolic risk factors and anthropometric parameters among the teaching faculty of Allama Iqbal Medical College and Jinnah Hospital Lahore (AIMC/JHL). To investigate the prevalence of metabolic syndrome and its components. METHODOLOGY: This cross-sectional study was conducted from December 2022 to July 2023 at AIMC/JHL. Faculty members (n=115), aged 30-60, were recruited by convenience sampling from basic and clinical departments. Metabolic syndrome was defined by ATP-III criteria. Means of quantitative variables were compared by student t-test. Chi-square was used to determine associations between nominal variables. RESULTS: Mean values of arterial blood pressure were significantly higher in males than females. Fasting hyperglycemia was present in 38.3% of participants. Decreased HDL, hypertriglyceridemia, hypertension, and central obesity were found in 65.2%, 24.3%, 34.8%, and 74.8% of participants, respectively. The prevalence of low HDL and central obesity was significantly higher among females; however, hypertriglyceridemia and hypertension were more prevalent among males. A significant correlation (r=0.241) was observed (p=0.009) between age and waist circumference. Pre-metabolic syndrome and metabolic syndrome were present in 38.3% and 43.5% of participants, respectively. CONCLUSION: An alarmingly high prevalence of metabolic syndrome and its components was observed among healthcare professionals who endeavor to treat similar diseases. This irony underscores the need for increased awareness and routine screening of metabolic syndrome among healthcare professionals